2018
DOI: 10.1007/s10620-018-4921-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Necrosis Factor-α-Induced Dermatological Complications in a Large Cohort of Inflammatory Bowel Disease Patients

Abstract: Dermatological manifestations occurred in almost one-third of our population. Infections were the most common complication, but anti-TNF-induced psoriasiform lesions were the most common cause for anti-TNF therapy definitive discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 34 publications
3
47
1
Order By: Relevance
“…For this reason, it is not consensual if another anti‐TNF‐ α should be attempted or a different therapeutic class should be considered. A wide range of recurrence rates after a second anti‐TNF‐ α agent was observed in different studies . In spite of an important risk of recurrence, two of the included studies recommended a switch to a second anti‐TNF‐ α drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is not consensual if another anti‐TNF‐ α should be attempted or a different therapeutic class should be considered. A wide range of recurrence rates after a second anti‐TNF‐ α agent was observed in different studies . In spite of an important risk of recurrence, two of the included studies recommended a switch to a second anti‐TNF‐ α drug.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of recurrence rates after a second anti-TNF-a agent was observed in different studies. 8,[15][16][17][20][21][22][23][24] In spite of an important risk of recurrence, two of the included studies 16,21 recommended a switch to a second anti-TNF-a drug. In our opinion, this is worth attempting, as other therapeutic options for IBD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, rheumatoid arthritis and Crohn's disease were found as the most common underlying illnesses (Joyau, Veyrac, Dixneuf, & Jolliet, ; Mazloom et al, ). Andrade et al conducted a retrospective observational study with 732 inflammatory bowel disease patients treated with anti‐TNF‐α agents and reported that the only treatment with adalimumab (OR = 8.894, p < .001) were independently associated with the development of psoriasiform lesions (Andrade et al, ). They also found that frequency of dermatological complications were as follow: infections (13.5%), psoriasiform lesions (5.3%), injection/infusion reactions (3.8%), skin cancer (0.5%), and miscellaneous (5.6%, 41/732), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most common were folliculitis in 38% of patients and abscesses in 31%. Psoriatic patients are likely to have less abscesses, since IBD diseases have specific extraintestinal manifestations and are also associated with hidradenitis suppurativa comorbidity which may be evaluated as folliculitis and abscesses [19].…”
Section: Mg Acute Hospitalization For Extensive Herpes Zoster In Dermentioning
confidence: 99%